Tattoo paste type speckle film and attaching process thereof

The tattoo-type speckle film with layered decoupling design solves the problems of speckle shedding and large errors in the measurement of large deformation structures, achieves high-precision deformation capture and complex surface adaptation, and is suitable for long-term monitoring of large deformation structures such as concrete.

CN120697418APending Publication Date: 2025-09-26TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510910160.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

The existing film-type speckle pattern has insufficient collaborative deformation ability in the measurement of large deformation structures, large strain transmission error, easy to fall off, difficulty in capturing the deformation characteristics of local high strain areas, and poor adaptability on complex surfaces, and cannot meet long-term monitoring needs.

Method used

The tattoo-type speckle film adopts a layered decoupling design, including a pattern layer, a transition layer and a water-soluble backing layer. The spot distribution is controlled by the Poisson disk algorithm and fixed with chemical cross-linked adhesive points. Combined with local anchoring and dynamic bonding processes, it ensures that the speckle maintains integrity and accuracy under large deformation conditions.

Benefits of technology

It significantly improves the strain transfer accuracy of large deformation measurement, can fully capture the deformation of the entire concrete structure, reduce strain transfer errors, improve the fitting accuracy and non-invasiveness on complex surfaces, and is suitable for batch experiment needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120697418A_ABST
    Figure CN120697418A_ABST
Patent Text Reader

Abstract

The invention discloses a tattooing paste type speckle film and an attaching process thereof, and belongs to the technical field of structural deformation measurement, and the tattooing paste type speckle film comprises a pattern layer, a transition layer and a water-soluble backing layer. The pattern layer comprises a PET film and ink spots printed on the surface of the PET film, and the black and white gray difference of the ink spots is greater than or equal to 220 levels; the transition layer comprises a TPU film, and the TPU film is provided with a honeycomb-shaped hollow structure; the water-soluble backing layer comprises a silicone oil paper substrate and a PVA water-soluble adhesive layer coated on the surface of the silicone oil paper substrate; the adhesive point is arranged in the center of the printing ink spot of the pattern layer and is fixed on the surface of the base material to be detected through a chemical crosslinking mechanism. According to the method, the core problem of cooperative failure of the speckles in large deformation measurement of concrete is systematically solved through a layering peelable structure of the tattoo paste type speckles, local adhesive point chemical crosslinking and a water transfer printing dynamic fitting process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of structural deformation measurement, and particularly relates to a tattoo-type speckle film and an attachment process thereof. Background Art

[0002] In the preparation and measurement of speckle patterns for large-deformation structural displacement field measurements, such as compressive failure in concrete ultimate strength testing, metal necking, and hydrogel stretching, existing integrated film-applied speckle patterns suffer from a core flaw: insufficient coordinated deformation capacity due to the full-film adhesive fixation and high film rigidity. Traditional spray-applied or film-applied speckle patterns are mismatched with the strain capacity of large-deformation substrates. Their physical adsorption method easily causes speckle detachment and cracking at high strains, and the significant difference in film stiffness from the material can easily lead to large strain transfer errors. Under large deformations, the entire film layer is subjected to tensile stress, making it prone to cracking and detachment at edges or weak points, especially on curved surfaces or areas of stress concentration. Furthermore, fixed-size speckle patterns are prone to feature loss due to excessive deformation, exceeding the subset matching accuracy of digital image correlation (DIC) technology, making it difficult to capture local strain gradients in high-strain regions such as crack tips.

[0003] In response to the above problems, the existing speckle preparation technology has obvious limitations: spray-type speckle has significant defects in the measurement of large deformation structures. It relies on an air spray gun or manual application of black and white paint to form speckles. The poor process stability leads to uneven spot size and blurred edges. The density cannot be accurately controlled and the probability of periodic overlap is high. It only adheres to complex surfaces such as concrete coarse aggregate protrusions and metal curved surfaces through physical adsorption. When the strain is slightly large, it falls off in large quantities. Especially in humid or high-temperature environments, it is easy to absorb water and soften, and the contrast decreases, which cannot meet long-term monitoring needs. The integrated film-based speckle pattern is fixed by gluing the entire film layer of PET / PP film. Although its accuracy is better than that of the spraying method, the elastic modulus of the film layer is ≥10MPa, which is seriously mismatched with the stiffness of materials such as hydrogel (0.1-1MPa) and concrete (<1MPa in the destruction stage). The strain transfer error is large. At the same time, when the deformation is large, the entire film layer is easily pulled and cracked and detached from the stress concentration area. For curved surfaces, the bubble rate is large. After the fixed-size speckle is stretched, the pixel coverage exceeds the sub-pixel matching accuracy range of the DIC algorithm, making it difficult to capture the deformation characteristics of local high-strain areas such as crack tips.

[0004] Therefore, it is necessary to propose a tattoo-type speckle film and its attachment process to solve the above problems. Summary of the Invention

[0005] In view of this, the object of the present invention is to provide a tattoo-type speckle film and its attachment process, which are used to solve the problem in the prior art that large deformation structure speckle cannot meet the measurement requirements of large deformation scenes.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a tattoo patch type speckle film, which comprises a pattern layer, a transition layer and a water-soluble backing layer arranged in sequence; The pattern layer includes a PET film and ink spots printed on the surface of the PET film, the black and white grayscale difference of the ink spots is ≥220 levels, and the diameter and density of the ink spots are controlled by a Poisson disk distribution algorithm; The transition layer includes a TPU film, and the TPU film is provided with a honeycomb hollow structure, and the aperture of the honeycomb hollow structure is 80-120 , hollowing rate 55%-65%, hole wall thickness 10-15 ; The water-soluble backing layer includes a silicone oil paper substrate and a PVA water-soluble adhesive layer coated on the surface of the silicone oil paper substrate. The thickness of the PVA water-soluble adhesive layer is 5-8 ; It also includes an adhesive point, which is arranged at the center of the ink spot of the pattern layer and is fixed to the surface of the substrate to be tested through a chemical cross-linking mechanism.

[0007] Furthermore, the ink of the ink spot is composed of carbon black with a purity of ≥99.5% and an average particle size of 0.5 The PET film has an elastic modulus of 800-1000 MPa and an elongation at break of ≥150%; and the minimum spacing between adjacent ink spots is ≥1.5 times the diameter of the ink spots.

[0008] Furthermore, the TPU film has a molecular weight of 200,000-300,000, an elastic modulus of 0.4-0.6 MPa, and an elongation at break of ≥350%; and the TPU film is added with a silane coupling agent KH-560 at a mass fraction of 3%.

[0009] Furthermore, the polymerization degree of the PVA water-soluble adhesive layer is 1750±50, and the alcoholysis degree is ≥98%; and the bottom surface of the silicone oil paper substrate is coated with a fluorosilane anti-sticking agent with a concentration of 2%.

[0010] Furthermore, the main agent of the adhesive point is a two-component epoxy adhesive, including component A epoxy resin E-51 and component B polyetheramine D-230, with a mass ratio of 10:3, and 5% mass fraction of nano-silica with a particle size of 20nm is added; the auxiliary agent of the adhesive point is a 3% concentration of silane coupling agent KH-550 ethanol solution.

[0011] A process for attaching a tattoo-type speckle film comprises the following steps: S1, using 80-grit sandpaper to polish the surface of the substrate to be tested until the surface roughness Ra of the substrate to be tested is 10-20 μm; and blowing away dust particles on the surface of the substrate to be tested; S2, spraying 3% silane coupling agent ethanol solution and drying at room temperature for 15 minutes; S3, immerse the speckle membrane in 25±1℃ deionized water to dissolve the PVA water-soluble adhesive layer for 35-40 seconds; S4: Place the wet speckle film on the surface of the substrate to be tested and push it evenly from the center to the edge with a scraper to puncture bubbles with a diameter greater than 1 mm. S5, when the ambient humidity is ≤ 60%, natural curing for 2 hours; when the ambient humidity is > 60%, use infrared lamp to heat to 40℃ and cure for 1 hour, where the infrared lamp power is 500W and the distance between the infrared lamp and the speckle film is 30cm; S6: After measurement, spray water mist and let it stand for 5 minutes. Then, peel off the backing layer and transition layer at a constant speed at an angle of 30°. The peeling speed is ≤5cm / s and the peeling force is 1-2N / 25mm.

[0012] Furthermore, the substrate to be tested includes concrete or metal plate.

[0013] Furthermore, when the substrate to be tested is concrete, in step S1, after polishing the surface of the substrate to be tested, the interface between the coarse aggregate and the cement mortar needs to be exposed, wherein the density of the ink spots set in the coarse aggregate area is greater than the density of the ink spots set in the cement mortar area, and the ink spots set in the coarse aggregate area adopt a triangular distribution, and the distance between adjacent ink spots is ≥1.5 times the diameter of the ink spots.

[0014] Furthermore, when there are protruding surfaces in the coarse aggregate area, they are first repaired and leveled with epoxy glue and quartz sand before the ink spots are attached.

[0015] The substrate to be measured in the present invention includes but is not limited to concrete, metal plates, or composite materials. Different substrates can be matched to the surface micromorphology differences of different substrates through differential density, ensuring the integrity of the speckle characteristics during large deformation measurement.

[0016] The beneficial effects of the present invention are: 1. This invention addresses the special needs of large deformation measurements, such as those in concrete ultimate strength tests, by developing a tattoo-like, removable speckle pattern technology. Through its innovative design of "layered decoupling, local anchoring, and dynamic synergy," it addresses the core challenges of traditional speckle pattern analysis in complex concrete deformation scenarios. 2. This invention systematically addresses the core challenge of speckle synergy failure in large-deformation measurement of concrete by utilizing a layered, peelable structure of tattoo-like speckle patches, chemical crosslinking of localized adhesive points, and a water transfer dynamic bonding process. The technical solution encompasses a full range of innovations, from material molecular design to engineering application, providing an efficient and reliable tool for studying the ultimate deformation performance of concrete structures. 3. In terms of large deformation tracking capability, the measurable strain range has been expanded from the limited range of traditional film-based methods to a higher range. This allows for complete capture of the entire deformation process of concrete, from microcrack initiation to through-failure. This effectively addresses the data loss issue after peak strain associated with traditional technologies, significantly reduces strain transfer errors, and accurately reflects the strain differences at the interface between coarse aggregate and matrix. 4. In terms of complex surface adaptability, it can adhere to any curved surface after the concrete specimen is damaged, including concave and convex surfaces with large crack widths. The bubble rate is significantly reduced, and the bonding accuracy is greatly improved compared to traditional films. The discontinuous spot design can avoid speckle deformation caused by coarse aggregate extrusion, significantly improving the spot shape retention rate and DIC matching success rate. 5. In terms of non-invasiveness and repeatability, the local adhesive process avoids large-scale damage to the concrete surface. After the experiment, the test blocks can be used for subsequent analysis. At the same time, the attachment efficiency is greatly improved, which greatly shortens the time compared to traditional manual spraying of speckles and is suitable for batch experiment needs. 6. Through the decoupling design of "local fixation of speckle + free deformation of hollow layer", the deformation characteristic points of the concrete surface are accurately anchored, and the membrane layer is allowed to deform with the overall deformation of the substrate, thereby solving the problem of coordinated failure of traditional membranes in large deformation scenarios.

[0017] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to make the purpose, technical solutions and beneficial effects of the present invention more clear, the present invention provides the following drawings for illustration: Figure 1 A side view of a speckle film attached to a substrate according to an embodiment of the present invention; Figure 2 Schematic diagram of the speckle film structure according to an embodiment of the present invention.

[0019] Reference numerals: pattern layer 1 , transition layer 2 , water-soluble backing layer 3 , adhesive points 4 , substrate 5 . DETAILED DESCRIPTION

[0020] like Figures 1 and 2 As shown, the present invention provides a tattoo patch type speckle film, comprising: a pattern layer 1, a transition layer 2 and a water-soluble backing layer 3 bonded in sequence; The pattern layer 1 comprises a PET film and ink spots printed on the surface of the PET film by a UV curing process, wherein the black and white grayscale difference of the ink spots is ≥220 levels; wherein the ink of the ink spots is composed of carbon black with a purity of ≥99.5% and an average particle size of 0.5 The titanium dioxide is mixed with the PET film in a mass ratio of 3:1, and the elastic modulus of the PET film is 800-1000 MPa, and the elongation at break is ≥150%. The ink spots are controlled in diameter and density using a Poisson disk distribution algorithm. The minimum spacing between adjacent ink spots is ≥1.5 times the ink spot diameter. The ink spot diameter is 2-3 mm in the small deformation area, with a density of 20-40 spots / cm², and 4-5 mm in the large deformation area, with a density of 5-10 spots / cm², ensuring that a single ink spot occupies 3-5 pixels in the image. The Poisson disk distribution algorithm is an improved spatial sampling method based on the Bridson algorithm. It achieves precise control of the speckle diameter and density in the speckle distribution by combining the construction of a grid index system with a ring sampling strategy. The algorithm first divides the sampling space into uniform grid units according to a preset minimum distance parameter, which is positively correlated with the target spot diameter, ensuring that there is at most one sampling point in each unit; then, candidate points are randomly generated in the annular area around the selected point, with the inner diameter being the minimum distance and the outer diameter being twice the minimum distance, and a fast grid search is used to determine whether the distance from the existing sampling points in the neighborhood meets the constraints, thereby ensuring that the generated speckle pattern is both random and maintains the minimum spacing. By converting the target spot density within a unit area into an average point spacing parameter and combining it with a functional relationship model between diameter and spacing, the algorithm can achieve precise control of the speckle density in the range of 20-50 / cm², while ensuring that the spot diameter is in the range of 10-500 Randomly distributed within the interval and edge sharpness ≤ 0.5 , significantly improving the feature matching accuracy and strain transfer reliability in digital image correlation (DIC) measurement.

[0021] The transition layer 2 includes a TPU (thermoplastic polyurethane) film, the molecular weight of the TPU film is 200,000-300,000, the elastic modulus is 0.4-0.6 MPa, and the elongation at break is ≥350%; the TPU film is added with a silane coupling agent (KH-560) with a mass fraction of 3% to improve the chemical compatibility with the concrete surface. The TPU film is prepared into a honeycomb hollow structure using laser micromachining technology, and the pore size of the honeycomb hollow structure is 80-120 , hollowing rate 55%-65%, hole wall thickness 10-15 ; So that the overall stiffness of the transition layer 2 is reduced by 40%-50%, and the strain transfer efficiency is increased to more than 95%; The water-soluble backing layer 3 includes a silicone oil paper substrate and a PVA (polyvinyl alcohol) water-soluble adhesive layer coated on the surface of the silicone oil paper substrate. The thickness of the PVA water-soluble adhesive layer is 5-8 The PVA water-soluble adhesive layer has a polymerization degree of 1750±50 and an alcoholysis degree ≥98% to ensure that it can be completely dissolved in deionized water at 25°C within 30 seconds; the bottom surface of the silicone oil paper substrate is coated with a fluorosilane anti-adhesive agent (concentration 2%), and the peel force is controlled at 1-2N / 25mm to prevent the water-soluble backing layer 3 from adhering to the transition layer 2 during attachment; The adhesive point 4 is also included. The adhesive point 4 is set at the center of the ink spot of the pattern layer 1 and is fixed to the surface of the substrate to be tested through a chemical cross-linking mechanism. The main agent of the adhesive point 4 is a two-component epoxy adhesive (component A: epoxy resin E-51, component B: polyetheramine D-230, mass ratio of 10:3), with 5% mass fraction of nano-silicon dioxide, particle size 20nm, added to improve the bonding strength; the auxiliary agent is a 3% concentration of silane coupling agent KH-550 ethanol solution, which is applied to the concrete surface before construction to react with the hydroxyl group in the cement hydration product to form Si-OC chemical bonds, and the interfacial bonding energy is increased to 25mJ / m²; the center of each ink spot is set to have a diameter of The 2mm circular adhesive dot 4 has its edge 0.5mm away from the edge of the ink spot to prevent the adhesive layer from overflowing and obscuring the pattern; the density of the adhesive dot 4 is consistent with the density of the ink spot, ensuring that there are 1-2 fixed anchor points per square centimeter of surface; the chemical crosslinking mechanism between the adhesive dot 4 and the concrete surface is as follows: the epoxy group (-CH2-CH-O-) in the epoxy adhesive chemically reacts with the calcium hydroxide (Ca(OH)2) in the concrete pores to form a stable -CO-Ca- bond; the silanol group (-SiOH) generated by the hydrolysis of the silane coupling agent condenses with the siloxy bond (-Si-O-Si-) on the concrete surface to form a covalent crosslinking network, ensuring that the adhesive dot does not fall off during large deformation.

[0022] In this solution, the hollow structure allows microcracks on the concrete surface to pass freely, preventing the membrane from hindering crack expansion and achieving deformation decoupling. The honeycomb pore walls undergo elastic deformation when stretched, reducing the stress concentration factor to one-third that of traditional films. It also provides moisture buffering, with the polar groups (-NHCOO-) in the TPU molecular chains absorbing moisture from the concrete pores, preventing the adhesive failure caused by water absorption and expansion of traditional adhesive layers. When a crack extends below the spot, the hollow structure of the transition layer 2 allows the crack to pass through. The adhesive point 4 breaks as the matrix on both sides of the crack separates, but the spot in the pattern layer 1 remains on both surfaces. Using a DIC algorithm to track the spot's displacement, continuous measurement of the crack width and growth rate is achieved.

[0023] The present invention also provides a process for attaching a tattoo-type speckle film to the surface of a substrate to be tested. When the substrate to be tested is concrete, the attachment process includes the following steps: S1: Use 80-grit sandpaper to polish the concrete surface, remove the floating slurry layer, and expose the interface between coarse aggregate and cement mortar. The roughness Ra is controlled at 10-20 ; Then blow to ensure that there is no dust particles on the surface; S2: Spray a 3% ethanol solution of silane coupling agent and dry it at room temperature for 15 minutes to increase the hydroxyl coverage of the concrete surface to more than 80% and enhance the chemical adsorption of adhesive point 4; S3: Immerse the speckle film in deionized water at 25±1°C to dissolve the PVA water-soluble adhesive layer for 35-40 seconds. At the same time, prevent the TPU film of the transition layer 2 from absorbing water and swelling. The water absorption rate of the TPU film should be less than 1%. S4: Aim the wet speckle film at the target area of ​​concrete, first applying it to the area with dense ink spots, such as the predicted starting point of the crack, and then use a soft rubber scraper to push it from the center to the edge at a uniform speed. For bubbles with a diameter greater than 1mm, puncture them with a needle and then push again; The ink speckle setting method for the coarse aggregate dense area is as follows: Aggregate distribution in concrete cross-sections was obtained through CT scanning. The location of coarse aggregate was automatically identified using a MATLAB algorithm. Standard spots were placed in the cement mortar area, while micro-spots were used in areas with dense aggregates, with an increased density. The micro-spots were distributed in a triangular pattern with a minimum spacing of 1 mm, ensuring that each spot corresponded to at least 3 pixels to avoid feature loss due to aggregate occlusion. Among them, for the protruding surface of coarse aggregate, you can first use epoxy glue and quartz sand to repair and smooth it, and then apply ink spots to ensure that the adhesive point 4 is in contact with the dense base to improve the bonding strength; Among them, for the surface attachment strategy after concrete damage: A 3D laser scanner was used to scan the surface of the damaged concrete, generating point cloud data with a point spacing of 0.5 mm. The surface model was then reconstructed using Geomagic software. Based on the surface curvature distribution, the surface was divided into three categories: convex, concave, and flat, and attachment strategies were designed for each: For convex surface areas, the stretchability and tightness of the film need to be considered when attaching materials. A block-by-block attachment process is used. First, the surface is scanned with a 3D laser scanner to generate point cloud data. After reconstructing the model using software, the convex surface is divided into strip areas along the curvature direction. Customized films that coincide with the plane of the strip areas are made. During attachment, the tension is controlled to avoid excessive stretching or wrinkling of the film. Due to the curvature of the convex surface, the attached material is prone to warping at the edges. Appropriate adhesives can be used to increase the adhesion of the edges or the material can be cut into a shape that fits the contour.

[0024] When attaching concave curved areas, gaps between the material and the surface and loose fit are likely to occur. Before attaching, the concave curved surface can be pre-treated, such as roughening it to increase the friction and adhesion between the material and the surface; divide the area through 3D modeling, and adopt a block attachment process, first attaching the bottom of the concave surface and then extending it outward along the edge.

[0025] Attaching to a flat surface is relatively simple. Before attaching, ensure that the surface is clean and tidy, free of dust and impurities. This can be pre-treated by washing or wiping. During the attachment process, rolling or other methods can be used to ensure full contact between the material and the surface, ensuring smooth attachment and avoiding bubbles or wrinkles.

[0026] S5, when the ambient humidity is ≤ 60%, natural curing for 2 hours; when the ambient humidity is > 60%, use infrared lamp to heat to 40℃ and cure for 1 hour, where the infrared lamp power is 500W and the distance between the infrared lamp and the speckle film is 30cm; S6: After the measurement, spray water mist and let it stand for 5 minutes to dissolve the remaining PVA water-soluble adhesive layer. Then, peel off the backing layer and transition layer 2 at a constant speed of 30°. The peeling speed should be ≤ 5 cm / s to avoid pulling on the ink spots and causing the adhesive points 4 to break. During attachment, the water-soluble backing layer 3 is temporarily bonded to the transition layer 2 through the PVA water-soluble adhesive layer to ensure the positioning accuracy of the ink spots on the pattern layer 1. After the measurement, water mist is sprayed to dissolve the residual adhesive layer, and the speckle film can be completely peeled off. The change in the roughness of the concrete surface is less than 5%, which does not affect the subsequent compressive strength test and achieves non-destructive peeling.

[0027] The morphological changes of ink spots under large deformation scenarios in this invention are based on the strain distribution simulation of concrete under compressive failure. The finite element model is established using the Drucker-Prager yield criterion. The spot morphology database under different strain gradients is generated using ImageJ software. The corresponding images are observed at an object distance of 500 mm using a camera with a resolution of 2 million pixels: When the strain is ≤100%, the ink spot morphology remains circular, with a diameter of 2-3 mm and a pixel ratio of 8-12 pixels; When the strain is 100%-200%, the ink spot morphology is pre-stretched into an ellipse with a major axis ratio of 1.3:1, and the major axis direction is consistent with the principal strain direction. After deformation, it returns to a circular shape, and the pixel ratio remains at 10-15 pixels; When the strain is greater than 200%, the ink spot is in the shape of a dumbbell, that is, round at both ends and a narrow neck in the middle, with a width of 0.5 mm. The ink spot maintains the characteristics of both ends when it breaks under tension to continuously provide matching points.

[0028] In step S6, after removing the backing layer and transition layer 2, the ink spot adhesion strength is tested using the cross-hatch method (ISO2409 standard). Specifically, a new blade is used to scratch 100 1 mm × 1 mm squares in the ink spot area. After removing the backing layer and transition layer 2, if the ink spot does not fall off after the number of squares is ≥ 95, it is judged to be qualified. Alternatively, a pulling method is used for testing. Specifically, a 10 mm diameter aluminum pulling head is used to bond the center of the ink spot through epoxy glue. If the pulling strength is ≥ 1.0 MPa and the fracture occurs in the concrete substrate rather than the adhesive layer, it is judged to be qualified.

[0029] The present invention attaches speckles to the surface of a standard concrete prism test block (100mm×100mm×300mm) and conducts a uniaxial compression test. A high-precision extensometer (accuracy 0.001mm) is used to measure the strain simultaneously: When the strain is ≤200%, the difference between the DIC measurement value and the extensometer value is ≤50 , consistency ≥98%; When the strain is 300%, the speckle retention rate is ≥90%, DIC can still track the deformation, and the traditional film-type speckle has completely fallen off.

[0030] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A tattoo-type speckle film, characterized in that: include: A pattern layer, a transition layer and a water-soluble backing layer are sequentially arranged; The pattern layer includes a PET film and ink spots printed on the surface of the PET film, the black and white grayscale difference of the ink spots is ≥220 levels, and the diameter and density of the ink spots are controlled by a Poisson disk distribution algorithm; The transition layer includes a TPU film, and the TPU film is provided with a honeycomb hollow structure, and the aperture of the honeycomb hollow structure is 80-120 , hollowing rate 55%-65%, hole wall thickness 10-15 ; The water-soluble backing layer includes a silicone oil paper substrate and a PVA water-soluble adhesive layer coated on the surface of the silicone oil paper substrate. The thickness of the PVA water-soluble adhesive layer is 5-8 ; It also includes an adhesive point, which is arranged at the center of the ink spot of the pattern layer and is fixed to the surface of the substrate to be tested through a chemical cross-linking mechanism.

2. The tattoo patch type speckle mask according to claim 1, characterized in that: The ink of the ink spot is composed of carbon black with a purity of ≥99.5% and an average particle size of 0.5 The PET film has an elastic modulus of 800-1000 MPa and an elongation at break of ≥150%; and the minimum spacing between adjacent ink spots is ≥1.5 times the diameter of the ink spots.

3. The tattoo patch type speckle mask according to claim 1, characterized in that: The TPU film has a molecular weight of 200,000-300,000, an elastic modulus of 0.4-0.6 MPa, and an elongation at break of ≥350%; and the TPU film is added with 3% by mass of a silane coupling agent KH-560.

4. The tattoo patch type speckle mask according to claim 1, characterized in that: The polymerization degree of the PVA water-soluble adhesive layer is 1750±50, and the alcoholysis degree is ≥98%; the bottom surface of the silicone oil paper substrate is coated with a fluorosilane anti-sticking agent with a concentration of 2%.

5. The tattoo patch type speckle mask according to claim 1, characterized in that: The main agent of the adhesive point is a two-component epoxy adhesive, including component A epoxy resin E-51 and component B polyetheramine D-230, with a mass ratio of 10:3, and 5% mass fraction of nano-silica with a particle size of 20nm is added; the auxiliary agent of the adhesive point is a 3% concentration of silane coupling agent KH-550 ethanol solution.

6. The process for attaching a tattoo-type speckle mask according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, using 80-grit sandpaper to polish the surface of the substrate to be tested until the surface roughness Ra of the substrate to be tested is 10-20 μm; and blowing away dust particles on the surface of the substrate to be tested; S2, spraying 3% silane coupling agent ethanol solution and drying at room temperature for 15 minutes; S3, immerse the speckle membrane in 25±1℃ deionized water to dissolve the PVA water-soluble adhesive layer for 35-40 seconds; S4: Place the wet speckle film on the surface of the substrate to be tested and push it evenly from the center to the edge with a scraper to puncture bubbles with a diameter greater than 1 mm. S5, when the ambient humidity is ≤ 60%, natural curing for 2 hours; when the ambient humidity is > 60%, use infrared lamp to heat to 40℃ and cure for 1 hour, where the infrared lamp power is 500W and the distance between the infrared lamp and the speckle film is 30cm; S6: After measurement, spray water mist and let it stand for 5 minutes. Then, peel off the backing layer and transition layer at a constant speed at an angle of 30°. The peeling speed is ≤5cm / s and the peeling force is 1-2N / 25mm.

7. The process for attaching the tattoo-type speckle mask according to claim 6, characterized in that: The substrate to be tested includes concrete or metal plate.

8. The process for attaching the tattoo-type speckle mask according to claim 7, characterized in that: When the substrate to be tested is concrete, in step S1, after polishing the surface of the substrate to be tested, the interface between the coarse aggregate and the cement mortar needs to be exposed, wherein the density of the ink spots set in the coarse aggregate area is greater than the density of the ink spots set in the cement mortar area, and the ink spots set in the coarse aggregate area adopt a triangular distribution, and the distance between adjacent ink spots is ≥1.5 times the diameter of the ink spots.

9. The process for attaching a tattoo-type speckle mask according to claim 8, characterized in that: When there are protruding surfaces in the coarse aggregate area, they should be repaired and smoothed with epoxy glue and quartz sand before the ink spots are attached.